2013
DOI: 10.1136/heartjnl-2013-304888
|View full text |Cite
|
Sign up to set email alerts
|

Heart failure in pregnant women with cardiac disease: data from the ROPAC

Abstract: Objective: Heart failure (HF) is one of the most important complications in pregnant women with heart disease, causing maternal and fetal mortality and morbidity. Methods: This is an international observational registry of patients with structural heart disease during pregnancy. Sixty hospitals in 28 countries enrolled 1321 women between 2007 and 2011. Pregnant women with valvular heart disease, congenital heart disease, ischaemic heart disease, or cardiomyopathy could be included. Main outcome measures were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
129
4
13

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 210 publications
(155 citation statements)
references
References 39 publications
9
129
4
13
Order By: Relevance
“…65 Data from the Registry On Pregnancy And Cardiac disease demonstrated that HF is a common complication in pregnant patients with cardiac disease (13%, of more than 1300 participants). 66 While the highest incidence of HF was found to be at the end of the second trimester or during childbirth, prevalence of HF was strongly associated with pre-eclampsia, premature birth and maternal and foetal mortality. However, patients with CHD had a relatively lower risk of developing HF compared with patients with valvular heart disease, ischaemic heart disease or cardiomyopathy.…”
Section: Pregnancy and Congenital Heart Diseasementioning
confidence: 95%
“…65 Data from the Registry On Pregnancy And Cardiac disease demonstrated that HF is a common complication in pregnant patients with cardiac disease (13%, of more than 1300 participants). 66 While the highest incidence of HF was found to be at the end of the second trimester or during childbirth, prevalence of HF was strongly associated with pre-eclampsia, premature birth and maternal and foetal mortality. However, patients with CHD had a relatively lower risk of developing HF compared with patients with valvular heart disease, ischaemic heart disease or cardiomyopathy.…”
Section: Pregnancy and Congenital Heart Diseasementioning
confidence: 95%
“…Several hemodynamic changes such as peripheral vasodilatation, increase in blood volume and cardiac output occur between the 1st and 2nd trimesters of pregnancy, and patients with known preexisting structural cardiac diseases typically present with clinical HF at this time [32,33]. In striking contrast, PPCM overwhelmingly presents during the postpartum period, and factors that modify the stresses of vaginal delivery such as caesarian section do not appear to modify the risk of developing the disease [33].…”
Section: Hemodynamic Burden Of Pregnancy Hypothesismentioning
confidence: 99%
“…It has been postulated that these physiological adaptations may also be implicated in the cardiomyopathic phenotype. 11 However, these changes typically occur during the first and second trimesters and not in the peripartum period. Even when additional stresses implicated in delivery, (such as caesarean section), have been accounted for, propensity for developing PPCM does not appear to be significantly raised.…”
Section: Pathophysiologymentioning
confidence: 99%